Perancangan Interior Lobby, Lounge, Bar Resort Inaya Putri Bali di Nusa Dua - Josephine Evelyna; Stephanus P Honggowidjaja; lucky basuki (Intra, 2015)
Indonesia as an archipelagic state owns a group of large and small islands that have the potential to become tourist attractions spots, including one of them is Bali Island. Viewing from this perspective, the interior design of this resort has become a supporting medium for the development of tourist attractions in Bali, especially in Nusa Dua. This project was implemented in response to the high interest of domestic and foreign tourist, which makes Bali a major tourist spot with its own appeal, which is the beauty of its beach and sea. This resort will eventually provoke the interest from domestic and foreign tourists to visit tourist attraction spots located around Nusa Dua. The results of this resort design consist of lobby, receptionist, luggage room, waiting area, staff room, lounge, and bar.